Hayekian economic policy - Lars P. Feld; Daniel Nientiedt (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2022)
What is the appropriate role of the state in economic policy-making? This paper shows that Friedrich Hayek, who is often considered a proponent of laissez-faire liberalism, offers three different answers to this problem. First, Hayek argues that the state should provide a legal framework for competitive markets. Second, he proposes to employ the rule of law criteria - generality, equality, and certainty - to distinguish permissible from non-permissible state interventions. Third, he rejects deliberate legislation and moves closer to the Misean idea of a minimal state. The paper considers these answers in light of Hayek's analysis of the knowledge problem. We suggest that a Hayekian approach to economic policy-making should focus on improving the framework of general rules that guide individual behavior, thereby enabling spontaneous ordering processes and reducing the epistemological burden placed on policy-makers.
Keywords: B31; D78; P16; 330; Friedrich Hayek; Rule-based economic policy; Spontaneous order; Knowledge problem; Cultural evolution